Book review: Coastal geology, by Juan A. Morales, 2022. Springer International Publishing, 455 pages. eBook price: 96,29 EUR, ISBN 978-3-030-96120-6 - Uścinowicz, Grzegorz (Geologos, 2023)
None provided.